MORPHOLOGICAL COMPARISON OF Hampala macrolepidota (Cyprinidae: Hampala) FROM SEVERAL POPULATIONS IN EASTERN JAVA - Amalia, Elok; Harahap, Muhammad Alfiandi Rachmad; Sufaichusan, Ifa; Dailami, Muhammad; Widodo, Maheno Sri; Faqih, Abd Rahem; Kusuma, Wahyu Endra (Journal of Environmental Engineering and Sustainable Technology, 2025)
The potential of freshwater fisheries in local species such as hampal fish (Hampala macrolepidota) presents several research gaps, particularly in specific localities. Research on H. macrolepidota in East Java may serve as a foundation for future management and development of local species, especially given that H. macrolepidota aquaculture is rarely carried out. Morphological studies based on meristics and morphometrics can be used for broodstock selection in H. macrolepidota domestication efforts. In this study, 21 Hampala specimens were assessed based on morphometrics and meristics, and analysed using a significance test, PCA and dendrogram. The analysis results by PCA and dendrogram showed morphometric differences in the Probolinggo and Banyuwangi populations compared with the four Brantas River populations. In contrast, based on meristics, the entire population does not show apparent differences based on the population. The clear differences demonstrated in the Probolinggo and Banyuwangi populations morphometrically indicate local adaptation due to differences in water conditions.